Factors associated with the development of research skills in graduate students - Núñez Lira, Luis Alberto (2020)
The purpose of the research was to determine the incidence of factors associated with the development of research skills in graduate students from public and private universities. A quantitative, basic-substantive, explanatory level methodology was used; the indeterminate population allowed the establishment of a stratified random sample of 384 master's and doctoral students. Multivariate logistic regression was used as a statistic. The results indicated a moderate incidence of 44.4%, according to Nagelkerke's pseudosquare of ,444, and, according to parameter (Wald) estimates, both variables influence the appropriate level.